1985
DOI: 10.1128/jb.162.1.92-97.1985
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and fusion of Streptococcus faecalis protoplasts

Abstract: Nonconjugative plasmids were transferred by protoplast fusion among Streptococcus faecalis strains and from Streptococcus sanguis to S. faecalis. S. faecalis protoplasts were also transformed with several different plasmids, including the Tn917 delivery vehicle pTV1. Transformation was reproducible, but low in frequency (10 6 transformants per viable protoplast). A new shuttle vector (pAM610), able to replicate in Escherichia coli and S. faecalis, was constructed and transformed into S. faecalis protoplasts. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Plasmid transfer occurred at a relatively high frequency when chromosomal marker transfers were undetectable under the same conditions. Similar results were recently obtained by Smith (19), who transferred plasmid pAMail between heterologous strains of S. faecalis by protoplast fusion. This suggests that the method could be of general use in introducing recombinant DNA into a variety of wild-type S. lactis strains.…”
Section: Methodssupporting
confidence: 87%
“…Plasmid transfer occurred at a relatively high frequency when chromosomal marker transfers were undetectable under the same conditions. Similar results were recently obtained by Smith (19), who transferred plasmid pAMail between heterologous strains of S. faecalis by protoplast fusion. This suggests that the method could be of general use in introducing recombinant DNA into a variety of wild-type S. lactis strains.…”
Section: Methodssupporting
confidence: 87%
“…The formation of bacterial protoplasts and the regeneration of their cell walls are essential features in the initial steps of development of either a protoplast transformation or a fusion system for strain improvement. Specific conditions for protoplast formation have been developed in plant cells (10,23,25), basidiomycetes (6), fungi (22), and many bacteria (4,5,8,12,15,16,18,19,24,27), including aerotolerant anaerobes such as Clostridium spp. (1,11,14).…”
mentioning
confidence: 99%
“…(12), Streptococcus spp. (6,17,25), and many other species have successfully been bred, it was suggested that the success of hybrid formation by protoplast fusion depends on the taxonomic proximity of the strains (13). Recent results obtained in this area of investigation, however, have shown that this may not be the case, as has been described for the interspecific protoplast fusion between Streptomycesfradiae and Streptomyces bikiensis (9,19) and between Streptococcus cremoris and Streptococcus lactis (18).…”
Section: Discussionmentioning
confidence: 99%